2016
DOI: 10.1021/acs.organomet.6b00372
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Mechanistic Variants in the Thermal Gas-Phase Activation of Methane

Abstract: In this review gas-phase studies conducted (mostly) at the Berlin laboratory of the authors are presented. The focus will be on describing mechanistic variants we (and others) came across recently in investigating the thermal activation of methane in the gas phase under idealized conditions. Typical examples include the discussion of those hydrogen-atom-transfer processes that do not follow the wellestablished conventional pathways in which oxyl radicals play a decisive role. This is the case when the spin is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
51
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 96 publications
0
51
0
2
Order By: Relevance
“…The comparison with the simulated IR spectra of isomers 5 ⋅(CO) 6 and 6 ⋅(CO) 6 clearly demonstrates that it is indeed the main‐group aluminum oxide which delivers its oxygen atom in the redox process. This observation, that main‐group oxides rather than transition‐metal oxides serve as the active site in various catalytic transformations, seems to be a rather general structural feature of quite a few metal oxide clusters; moreover, as shown in a different context, these oxyl centers also play a decisive role in the thermal activation of strong C−H bonds, for example, cleavage of methane's C−H bond, by metal‐attached oxyl groups ,,…”
Section: Identification Of a Catalyst's Active Sitementioning
confidence: 87%
“…The comparison with the simulated IR spectra of isomers 5 ⋅(CO) 6 and 6 ⋅(CO) 6 clearly demonstrates that it is indeed the main‐group aluminum oxide which delivers its oxygen atom in the redox process. This observation, that main‐group oxides rather than transition‐metal oxides serve as the active site in various catalytic transformations, seems to be a rather general structural feature of quite a few metal oxide clusters; moreover, as shown in a different context, these oxyl centers also play a decisive role in the thermal activation of strong C−H bonds, for example, cleavage of methane's C−H bond, by metal‐attached oxyl groups ,,…”
Section: Identification Of a Catalyst's Active Sitementioning
confidence: 87%
“…[3b, 5] In the context of methane C À H bond activation, classical hydrogen-atom transfer (HAT), [5c,6] proton-coupled electron transfer (PCET), [7] and hydride transfer (HT) [8] scenarios have been identified as mechanistic variants. [9] Zinc complexes play ar ather important role as stoichiometric reagents or catalysts in both large-scale and biological transformations, [10] and gas-phase studies have resolved some of the mechanistic puzzles. [11] Herein, we will show how ligation of bare [ZnO]C + with CH 3 CN profoundly changes the selectivity of [ZnO]C + towards methane under thermal conditions;m echanistic insight is provided by high-level quantum chemical calculations.F urther,w ew ill describe the root cause of the mechanistic switch as being induced by both the ligand effect and an oriented external electric field.…”
mentioning
confidence: 99%
“…[6] An alternative tool is,f or example,t he analysis of deformation energies,a sproposed by the group of Shaik. [11] Yet DFT does frequently allow for the qualitative,a nd even quantitative,d escription of complex chemical transformations (including reactions involving PCET) [12] and its software implementations have by now reached as tate of maturity allowing for in-depth studies of large (and more importantly, experimentally accessible) systems.A nalysis of stationary points for ac PCET reaction of an Fe III ÀOH complex with TEMPOH [13] prompted us to explore the possibilities of monitoring electron flow in such PCET transformations using the IBO representation, to reveal their reaction mechanisms directly. With modern software and computers it is absolutely possible to determine approximate but qualitatively correct (Kohn-Sham) electronic wave functions for most of the involved species and, based on those,a lso determine all likely intrinsic reaction paths for possible PCET events and compare their barriers.O nce the most favorable reaction path has been determined, it should be possible to simply analyze the obtained trajectory of the ground state Nelectron wave function directly to clarify the concrete nature of the process.A fter all, the N-electron wave function contains all information about the N-electron system which is physically observable.A dditionally,r ecently introduced analytic methods,s uch as the intrinsic bond orbital (IBO) [8] transformation, provide an exact representation of any Kohn-Sham density functional theory (DFT) wavefunction, which is well amenable to the analysis of electronic structure changes in intuitive terms.W ehave previously demonstrated that the changes which IBOs undergo along agiven reaction path can be linked to curly arrows [9] and are indeed suitable for the investigation of C(sp 3 )ÀHa ctivation reactions.…”
mentioning
confidence: 99%
“…[10] These previously investigated reactions were of closed shell nature and only involved the movement of electron pairs.Asaresult, previous investigations did not give rise to the challenges that open shell systems,e specially in homolytic bond cleavage, pose to most computational chemistry methods,a nd in particular to single-reference methods such as DFT. [11] Yet DFT does frequently allow for the qualitative,a nd even quantitative,d escription of complex chemical transformations (including reactions involving PCET) [12] and its software implementations have by now reached as tate of maturity allowing for in-depth studies of large (and more importantly, experimentally accessible) systems.A nalysis of stationary points for ac PCET reaction of an Fe III ÀOH complex with TEMPOH [13] prompted us to explore the possibilities of monitoring electron flow in such PCET transformations using the IBO representation, to reveal their reaction mechanisms directly.…”
mentioning
confidence: 99%